Membrane-associated proteomics of chickpea identifies Sad1/UNC-84 protein (CaSUN1), a novel component of dehydration signaling - Jaiswal, Dinesh Kumar (Nature Publishing Group, 2014)
Dehydration affects almost all the physiological processes including those that result in the accumulation of misfolded proteins in the endoplasmic reticulum (ER), which in turn elicits a highly conserved signaling, the unfolded protein response (UPR). We investigated the dehydration-responsive membrane-associated proteome of a legume, chickpea, by 2-DE coupled with mass spectrometry. A total of 184 protein spots were significantly altered over a dehydration treatment of 120 h. Among the differentially expressed proteins, a non-canonical SUN domain protein, designated CaSUN1 (Cicer arietinum Sad1/UNC-84), was identified. CaSUN1 localized to the nuclear membrane and ER, besides small vacuolar vesicles. The transcripts were downregulated by both abiotic and biotic stresses, but not by abscisic acid treatment. Overexpression of CaSUN1 conferred stress tolerance in transgenic Arabidopsis. Furthermore, functional complementation of the yeast mutant, slp1, could rescue its growth defects. We propose that the function of CaSUN1 in stress response might be regulated via UPR signaling.